Analisis Kesulitan Pembelajaran Daring Mahasiswa Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Surakarta - Erviana Putri Kristiyantini (Jurnal Bidang Pendidikan Dasar, 2022)
The Covid-19 pandemic has changed the learning model in various countries. Learning that was originally carried out face-to-face has now become online learning. Universities are better prepared to face online learning, because they are used to using e-learning at least blended learning. This study aims to determine the difficulties and solutions experienced by PGSD UMS students during online learning. This research uses descriptive qualitative method. Collecting data through interviews, observation and documentation. The subjects of this study were 26 at the Muhammadiyah University of Surakarta. The results of this study explain that in carrying out online learning, PGSD UMS students experience various difficulties, namely difficulty understanding the material, difficulties with internet network facilities and so on. In addition, there are various solutions from UMS PGSD students, namely students trying to understand the material, difficulties with internet networks, students looking for places with good networks and soon